PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS DI MEDIASI OLEH KEPUASAN PELANGGAN PADA JASA TRANSPORTASI PT. FAJAR RIAU WISATA DUMAI-PEKANBARU - Nisyah, Habibah Tun; Isyandi, B.; Wijayanto, Gatot (Komunitas Manajemen Kompetitif, 2023)
This study aims to see and determine the direct and indirect effects of price and service quality on loyalty mediated by customer satisfaction. The population in this study are customers (passengers) of PT. Fajar Riau Tourism, totaling 19,876 by using a questionnaire. This research is a quantitative research with a descriptive design. The method used in this study aims to see the relationship between variables by using probability sampling which gives equal opportunities for each element of the population to be selected as members of the sample. With the criteria for passengers who are over 17 years old and have used transportation services more than once. Determination of the sample in this study using the tables of Isaac and Michael from certain populations with a level of 10%. Price has a significant positive effect on customer satisfaction and customer loyalty. Service quality has a significant positive effect on customer satisfaction and customer loyalty. Customer satisfaction has a significant positive effect on loyalty. Customer satisfaction is able to mediate the effect of price on loyalty. Customer satisfaction is able to mediate the effect of service quality on loyalty. Keywords: Price, Service Quality, Customer Satisfaction and Loyalty